Behavioral Geography: an Ecoliteracy Perspective and Critical Thinking Skills in Men and Women - Nadiroh Nadiroh; Uswatun Hasanah; Vania Zulfa (Indonesian Journal of Geography, 2019)
This study aims at explaining the behavior of students of the biology-Jakarta State University study program on environmental preservation in the perspective of ecoliteracy and critical thinking skills. Ecoliteracy is an understanding and behavior or the action of a person towards the environment. The results of the study show that there is no effect of the interaction between ecoliteracy and thinking Skills. In addition, there is also no interaction between ecoliteracy and gender. This study supports previous relevant research and provides new empirical information that ecoliteracy and critical thinking skills are the causes of someone contributing to preserving the environment. However, the influence of ecoliteracy interactions and critical thinking skills is not significant. In addition, the interaction in the ecoliteracy and gender perspective needs to be ignored because both of them make the same contribution. Therefore, the application of ecoliteracy must begin early. The application of ecoliteracy can also be integrated into the media that are currently developing rapidly. So that at the university level, the concept of ecoliteracy has emerged in a more creative and innovative form by initiating new innovations in the more advanced environment.